The reliability of a 30-s sprint test on the Wattbike cycle ergometer - Driller, M. W.; Argus, C. K.; Shing , C. M. (International Journal of Sports Physiology and Performance, 2013)
Purpose: To determine the reliability of a 30-s sprint cycle test on the Wattbike cycle ergometer. Methods: Over 3 consecutive weeks, 11 highly trained cyclists (mean ± SD; age 31 ± 6 y, mass 74.6 ± 10.6 kg, height 180.5 ± 8.1cm) completed four 30-s maximal sprints on a Wattbike ergometer after a standardized warmup. The sprint test implemented a "rolling start" that consisted of a 60-s preload (at an intensity of 4.5 W/ kg) before the 30-s maximal sprint. Variables determined across the duration of the sprint were peak power (Wpeak), mean power (Wmean), W/kg, mean cadence (rpm), maximum heart rate (n = 10), and postexercise blood lactate. Results: The average intraclass correlation coefficients between trials (2v1, 3v2, 4v3, 4v1) were Wpeak .97 (90%CI .94-.99), Wmean .99 (90%CI .97-1.00), W/kg .96 (90%CI .91-.98), mean cadence .96 (90%CI .92-.99), maximum heart rate .99 (90%CI .97-.99), and postexercise blood lactate .94 (90%CI .87-.98). The average typical error of measurement (expressed as a CV% and absolute value between trials—2v1, 3v2, 4v3, 4v1) was Wpeak 4.9%, 52.7 W; Wmean 2.4%, 19.2 W; W/kg 2.3%, 0.18 W/kg; mean cadence 1.4%, 1.6 rpm; maximum heart rate 0.9%, 1.6 beats/min; and postexercise blood lactate 4.6%, 0.48 mmol/L. Conclusion: A 30-s sprint test on the Wattbike cycle ergometer is highly reproducible in trained cyclists.